The Evaluation of Physiological Index Changes and Safety Work of Female Medical Staff With Different Medical Protection Standards in the Ward of COVID-19 - Zhao, Min; Zhao, Jianhui; Yan, Junbing; Gao, Xiaoye (Frontiers in Medicine, 2022)
Abstract Background: Effective personal protective equipment (PPE) contribute to the prevention of COVID-19 infection. However, it is necessary to evaluate the potential risk of different medical protections in the isolation ward of COVID-19. Objectives: We aimed to explore the dynamics in physiological indexes of medical staff under primary and secondary PPE in the isolation ward of COVID-19, and provide the scientific basis for determining the safe work strategy. Methods：30 female nurses were selected to simulate medical work under the primary or secondary PPE respectively. The oral temperature, axillary temperature, heart rate, respiratory rate, blood oxygen saturation and blood pressure were measured and recorded every 20 min. The subjective adverse symptoms were recorded every 30 min. The blood glucose and weight of the individuals were measured and recorded before and after the trial. Results: The results indicated that the median trial persistence time in the participants with moderate-intensity work wearing the secondary PPE (70.0 min) was much lower than that with moderate-intensity work wearing the primary PPE (180 min) and with light-intensity work wearing the primary PPE (110 min) (P < 0.05). Importantly, the heart rate, oral/ axillary temperature and respiratory rate of physiological indexes of the participants under moderate-intensity work wearing the secondary PPE increased significantly faster than the primary PPE (P < 0.001), while blood oxygen saturation decreased significantly faster than the primary PPE (P < 0.001). Besides, the proportions of subjective adverse symptoms (including dry mouth, dizziness, palpitations and anhelation) were much higher than primary PPE (P < 0.001). The average sweat volume and blood glucose consumption of participants under moderate-intensity work wearing primary PPE were higher than secondary PPE (P < 0.001). Conclusion: The combination of an exacerbated workload and secondary PPE worn by COVID-19 healthcare workers increases the change in physiological indicators and cases the adverse symptoms, which can affect and even suspend their medical work. For any medical institution, there is room for improvement in terms of bioethics of a 'Job Well Done' to reduce the risks of medical activities under secondary PPE.